POLA KOMUNIKASI LEADER CENTER NOISE DALAM MENDUKUNG TIM PERSIS SOLO DI TRIBUN B6 STADION MANAHAN SURAKARTA UNTUK MENINGKATKAN KREDIBILITAS - Ramadani, Alif; Wangi, Maya Sekar; Itasari, Andri Astuti (Solidaritas, 2024)
This study aims to: To find out the pattern of group communication between Leader Center Noise, Center Noise, and Firm Hooligan at the Tribune B6 Manahan stadium in Surakarta to increase credibility.This type of research is qualitative research using descriptive study methods. Data collection techniques used in the form of interviews and participatory observation. The selection of this research method is based on the phenomena found, from the phenomenon of facts, such as the knowledge of the subject under study based on an incident or experience, so that the results of descriptive data are obtained in the form of written or spoken words from the people or observed behavior.The object of this research is Center Noise and representatives from each company as the main data source. Researchers conducted a search for information from interviews conducted on informants. The main data source was obtained from the Noise Center named Ramadhan Eka Admaja from the Surakarta Offender Firm. Other data sources were obtained from company representatives, totaling ten people. The researcher also collected secondary data in the form of photos and video observations at the B6 Stand at the Manahan Stadium, Surakarta. From the interview results, the group communication pattern that occurs between Center Noise, Center Noise, and Firm is a group communication pattern, namely the primary communication pattern in the form of verbal symbols including language and non-verbal symbols including limb gestures, secondary communication patterns in the form of communication with technology, linear communication patterns in the form of planning, and circular communication patterns in the form of reciprocal responses. Through communication that is established, it is able to increase the credibility of the Persis Solo team.